2001
DOI: 10.1016/s0038-1098(01)00207-1
|View full text |Cite
|
Sign up to set email alerts
|

Substitution effect of Zn and Cu in MgB2 on Tc and structure

Abstract: The investigation of Zn substitution in MgB 2 polycrystalline samples shows that about 0.1 Zn can be substituted in the structure of Mg deficient samples while it can not be substituted in stoichiometric MgB 2 . As a result of the isovalent Zn substitution into the Mg position of Mg deficient samples the a and c lattice constants increase by about 0.17% and 0.2% respectively. Susceptibility measurements show a slight lowering of T c by about 0.5 K for 0.05 Zn, which decreases to 0.2 K for 0.1 Zn substitution. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 10 publications
2
53
1
Order By: Relevance
“…Cheng et al who observed very recently that the solubility limit of Ag at Mg site is around x = 0.005 [37]. For Zn, and contrary to Kazakov et al [22], and even using such severe conditions like thus of HP-HT synthesis, we found no evidence for a change in the a and c lattice parameters in our samples ( The defects made up of the grains of secondary phases (for Na, Ca, Cu, Zn and Ag) could act as pinning centres and may increase the critical current. However, the magnetisation measurements (VSM) show that these inclusions do not really improve j c nor its magnetic field dependence.…”
Section: Hp-ht Synthesismentioning
confidence: 96%
“…Cheng et al who observed very recently that the solubility limit of Ag at Mg site is around x = 0.005 [37]. For Zn, and contrary to Kazakov et al [22], and even using such severe conditions like thus of HP-HT synthesis, we found no evidence for a change in the a and c lattice parameters in our samples ( The defects made up of the grains of secondary phases (for Na, Ca, Cu, Zn and Ag) could act as pinning centres and may increase the critical current. However, the magnetisation measurements (VSM) show that these inclusions do not really improve j c nor its magnetic field dependence.…”
Section: Hp-ht Synthesismentioning
confidence: 96%
“…The lattice parameters of MgB 2 obtained by XRD measurement and Rietveld refinement vary only slightly between samples, and any significant Cu atomic substitution in MgB 2 can be excluded. It has been previously reported that copper has no solubility in MgB 2 [17] and of course it is present in all the samples tested here (with or without added copper in the core). Unreacted amorphous boron remaining in the samples could not be detected by our XRD measurements, but the mass fractions of the detected phases obtained from Rietveld refinement were corrected based on the known ratio between Mg and B in the starting powders.…”
Section: Cu Addition Effectmentioning
confidence: 54%
“…Our observation points to possible T c increase if a could be expanded. 20 In fact, Medvedeva et al predicted that higher T c may be obtained in lattice expanded case such as the hypothetical CaB 2 .…”
Section: Resultsmentioning
confidence: 99%